Studi Kritik Hadis Kebermanfaatan Terhadap Sesama Yang Populer Di Tingkat Pendidikan Dasar - Shofiyah, Shofiyah; Azizah, Nur (Awwaliyah: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2021)
Some certain hadiths related to daily life have been quite popular among society. Yet, the validity is still being questioned. One of them is the hadith about being beneficial for others. Further studies are thus required to confirm its quality either in terms of narration or context of hadith content. These hadiths are Mu'jam al-Ausath, Mu’jam al-Kabir, Musnad Syihāb, Al-Khila’iyyāt, Al-Futwah and Fawā’id al-‘Iraqiyyīn. They are considered to be dha’if, since there is a majhul narrator in the path of Jabir, namely ‘Alī ibn Bahrām and Abdurrahman ibn‘ Umar al-Shaffār. In Mutabi’, four lines narrating from Jabir are considered dha'īf due to the presence of majhul narrators (Ali ibn Bahram, Abdullah ibn Salih al-Madaini, Abu Fadhl ar-Roshofi, Abu Muhammad ibn Aban) Abu Muhammad Abdullah ibn Aban Majhul Hal and 'Ain, Abu Bakr Muhammad ibn Ahmad al-Haidari Majhul hal and Abu Muhammad Isma'il ibn Raja'Majhul Hal and maudhu' (Amr ibn Bakr as-Saksaky). Nonetheless, in the term of Matan, these hadiths have the shahih signification as being beneficial is very precious for anyone existence. It is such reciprocity and balance in life. The state of being beneficial can also be interpreted as providing service or helping human beings, as Allah SWT says in Surat al-Maidah verse 2.